Advanced gallbladder cancer accompanied with cancer-associated dermatomyositis: A case report and literature review. Issue 27 (8th July 2022) - Kuroda, Haruka; Yamaguchi, Atsushi; Sugata, Shuhei; Hamada, Takuro; Moriuchi, Riho; Wada, Kaoru; Tamaru, Yuzuru; Kusunoki, Ryusaku; Kuwai, Toshio; Kouno, Hirotaka; Kurashige, Takashi; Torii, Tsuyoshi; et al.
Abstract : Rationale: Muscle weakness due to cancer-associated dermatomyositis (CADM) can be misdiagnosed as cancer cachexia and disuse atrophy. Patient concerns: A 75-year-old female was admitted to our institute with muscle weakness, dysphagia, and suspected gallbladder cancer. Computed tomography and cytopathological examinations of the liver biopsy and fine-needle aspiration from swollen lymph nodes using endoscopic ultrasonography revealed cancer in the gallbladder body and metastasis to the lymph nodes around the abdominal aorta. We avoided the administration of anticancer drugs due to her poor general condition. Diagnosis: Subsequently, we diagnosed her with muscle weakness and dysphagia as a result of CADM using species from muscle and skin biopsy. Interventions and Outcomes: Prednisolone therapy and anticancer agents partially improved the patient symptoms. Lessons: CADM is reported to be associated with a high incidence of dysphagia, which may aid in the diagnosis of this disease.